Pengaruh Pijat Oksitosin terhadap Kelancaran Produksi Asi pada Ibu Post Partum di Klinik Lidya Kabupaten Deli Serdang - Tarida Irmayani Marbun; Marta Armita Silaban (Lembaga Pengembangan Kinerja Dosen, 2025)
Background:Breastfeeding is expected to help achieve SDGs goal 3, target 2, which is to reduce neonatal mortality to at least 12 per 1,000 live births in all countries by 2030 and stop unnecessary deaths of newborns and children under five. Encouraging healthy breastfeeding is essential to prevent more than 820,000 deaths of children under five each year. Oxytocin massage has been shown to increase the sensation of relaxation, improve sleep quality and comfort, reduce pain and tension, and help increase prolactin and oxytocin levels, which in turn increase breast milk production. Research Method:The research design used the Pre Experimental Design method, namely with the form of a One Group pretest and posttest design without a control group. This study used purposive sampling, with a sample size of 22 respondents. Data analysis used univariate and bivariate. Result:This study showed that the value before oxytocin massage was 16.14 and after oxytocin massage the mean was 27.73. The conclusion of the study shows that the results of the experimental test have a significant value with a p value of 0.000 <0.05. This shows that there is a significant gap in breast milk production between before and after oxytocin massage. Suggestion: It is hoped that midwives at the Lidya Clinic can use this study as input to support increased breast milk production in mothers, especially those in the postpartum period.